2017
DOI: 10.1200/jgo.2016.008011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Individual Patient Data to Assess the Sensitivity of Cervical Cytology for Diagnosis of Cervical Cancer in Low- and Middle-Income Countries

Abstract: PurposeTo assess the sensitivity of cervical cytology to cancer by pooling individual patient cytology results from cancers diagnosed in studies that assessed cervical screening in low- and middle-income countries.MethodsTwo authors reviewed studies identified through PubMed and Embase databases. We included studies that reported cervical cytology in which at least one woman was diagnosed with cervical cancer and in which abnormal cytology results were investigated at colposcopy and through a histologic sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 24 The systematic review and meta-analysis in low and middle-income countries included more than 700 cervical cancers from 23 studies and found pooled sensitivity of cytology for cancer 79.4% at a cut-off HSIL+. 34 On the other hand, Greek study authors reported about a very low sensitivity of cytology, 13.6% at cut-off HSIL. 35 …”
Section: Discussionmentioning
confidence: 98%
“… 24 The systematic review and meta-analysis in low and middle-income countries included more than 700 cervical cancers from 23 studies and found pooled sensitivity of cytology for cancer 79.4% at a cut-off HSIL+. 34 On the other hand, Greek study authors reported about a very low sensitivity of cytology, 13.6% at cut-off HSIL. 35 …”
Section: Discussionmentioning
confidence: 98%
“…Triage with cytopathology is proposed in developing (middle-income) countries where infrastructure exists with experience of screening. 44 Castanon et al 45 found that cytopathology at a cutoff for high-grade squamous intraepithelial lesions or worse had a sensitivity of 79% for cancer. Many HICs are moving to primary screening by HPV testing.…”
Section: Methodsmentioning
confidence: 99%
“…However, this review did not show results for other parameters, such as specificity, diagnostic OR, AUC on SROC. The estimated values of overall abnormal cytology and LSIL were not found in the previous review 40…”
Section: Discussionmentioning
confidence: 60%
“…In summary, the superiority of the HPV test for accurately diagnosing SIL or SqCC in the uterine cervix cannot be proven in the previous DTA review. In addition, in other DTA review,40 the pooled sensitivity of cytology with HSIL or worse was 79.4% for predicting cancer. However, this review did not show results for other parameters, such as specificity, diagnostic OR, AUC on SROC.…”
Section: Discussionmentioning
confidence: 86%